Antitrypanosomal acetylene fatty acid derivatives from the seeds of porcelia macrocarpa (annonaceae) - Santos, Luciana de A. [UNESP]; Cavalheiro, Alberto J. [UNESP]; Tempone, Andre G.; Correa, Daniela S.; Alexandre, Tatiana R.; Quintiliano, Natalia F.; Rodrigues-Oliveira, Andre F.; Oliveira-Silva, Diogo; Martins, Roberto Carlos C.; Lago, Joao Henrique G. (Mdpi Ag, 2015)
Chagas'disease is caused by a parasitic protozoan and affects the poorest population in the world, causing high mortality and morbidity. As a result of the toxicity and long duration of current treatments, the discovery of novel and more efficacious drugs is crucial. In this work, the hexane extract from seeds of Porcelia macrocarpa R.E. Fries (Annonaceae) displayed in vitro antitrypanosomal activity against trypomastigote forms of T. cruzi by the colorimetric MTT assay (IC50 of 65.44 g/mL). Using chromatographic fractionation over SiO2, this extract afforded a fraction composed by one active compound (IC50 of 10.70 mu g/mL), which was chemically characterized as 12,14-octadecadiynoic acid (macrocarpic acid). Additionally, two new inactive acetylene compounds (,'-dimacro-carpoyl--oleylglycerol and -macrocarpoyl-'-oleylglycerol) were also isolated from the hexane extract. The complete characterization of the isolated compounds was performed by analysis of NMR and MS data as well as preparation of derivatives.
Keywords: Porcelia macrocarpa; Annonaceae; Acetylene derivatives; Trypanosoma cruzi